Perjuangan Jurnalis Lokal dalam Memberitakan Covid-19 - Vinisa Nurul Aisyah (ETTISAL : Journal of Communication, 2023)
Information is a primary need in dealing with COVID-19. In this case, local media is one of the closest sources of information and controls problems in local communities, especially during the pandemic. For this reason, this study aims to analyze how local journalists as communicators in mass communication produce messages to overcome the infodemic during the COVID-19 pandemic. This study used Schoemaker and Reese's hierarchy of influence model to dissect the process of producing messages for local journalists. This study employed qualitative methods through in-depth interviews and interactive analysis. The findings in this study revealed that in producing news during a pandemic, journalists experienced various obstacles. These obstacles were spread across three levels: first, the personal level, which is related to journalists' perception and lack of understanding of COVID-19. The second is the routine practice level, including the lack of a verification process and the stuttering technology use. Third, the organization level is related to guaranteeing the welfare and safety of journalists, which is not optimal. This study recommends a solution for integrating technology in the news production process and guaranteeing journalists' welfare, which is still a classic problem in Indonesia.